Unifying Islamic Time: A Contextualised Fiqh Analysis of the Unified Global Hijri Calendar Between Uṣūl Al-Fiqh, Maqāṣid Al-Sharīʿah, and Transnational Legal Authority - Friska Linia Sari; Bakhouya Driss; Badrun Taman (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
The persistent fragmentation of Hijri month determination across Muslim-majority states constitutes a normative and juridical problem whose resolution has eluded both classical fiqh and modern Islamic institutions. Existing scholarship has addressed the issue predominantly through maqāṣid analysis or empirical policy studies, without producing a systematic reconstruction of the problem within the integrated framework of uṣūl al-fiqh methodology, maqāṣid al-sharīʿah, and the theory of transnational legal authority (wilāyat al-ḥukm). This study critically analyses the juridical construction, normative legitimacy, and legal implications of the Unified Global Hijri Calendar (UGHK) within the contemporary uṣūl al-fiqh framework, with particular attention to the dialectic between scriptural authority and astronomical science. Normative legal research was conducted using a conceptual approach, combining analysis of primary Islamic legal sources (Qurʾān, ḥadīth, classical fiqh compendia), contemporary scholarly discourse, and outputs of international collective ijtihād forums, including the 2016 Istanbul Congress. Data were processed through descriptive-analytical and argumentative techniques with deductive-comparative reasoning across classical and contemporary juristic positions. The study finds that UGHK construction is jurisprudentially grounded through: (1) a taʿaqqulī reinterpretation of rukyah as wasīlah rather than maqṣūd li-dhātihi, enabling the integration of precise astronomical calculation; (2) a contextualised reinterpretation of ikhtilāf al-maṭāliʿ responsive to globalised information access; and (3) maqāṣid-based legitimation across ḥifẓ al-dīn, ḥifẓ al-māl, and ḥifẓ al-ʿaql. This study is the first to integrate all three analytical axes — uṣūl al-fiqh methodology, maqāṣid al-sharīʿah, and wilāyat al-ḥukm transnational theory — into a unified juridical framework for UGHK legitimation, offering a more structurally coherent alternative to the fragmented approaches prevailing in the literature